A study of knowledge, belief and attitude on neonatal (jaundice among Malay pregnant mothers who attend antenatal clinics in Seberang Perai Utara, 1994 - Normala Abdul Wahid,; Khalib Abd Latip, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
This is a cross-sectional study to identify level of knowledge, belief and attitude on neonatal jaundice among Malay pregnant mothers who live in Seberang Perai Utara state. A total of 150 pregnant mothers attended antenatal clinics in Seberang Perai Utara, were chosen by systematic random sampling and were interviewed using a pretested questionaire. Results showed about 50.0% of the respondent had inadequate general knowledge on neonatal jaundice, especially the knowledge on complications and identifying the best method of jaundice detection. There were significance finding between general knowledge on neonatal jaundice and the gravida, para and history of previous neonatal jaundice (p<0.05). About half of the respondent had combination of belief in causes of neonatal jaundice. Majority were also found believing in the usage of combination of treatment for neonatal jaundice. There were significant association between general knowledge on neonatal jaundice and belief in combination of causes, belief in harmful treatment and belief in combination of treatment (p<0.05). Positivity attitude to seek treatment was found to be significant with belief in supernatural causes of neonatal jaundice (p<0.05). In conclusion, there is a need to increase the level of knowledge among Malay pregnant mothers in hoping that the increase in knowledge and awareness will influence the belief system on the right concept of causes and treatment of neonatal jaundice.